2011
DOI: 10.1136/acupmed-2011-010021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Electrodermal Activity at Acupuncture Points: A Narrative Review

Abstract: Objectives To provide an in-depth analysis of seven well-reported studies that examined electrodermal activity (EDA) at acupuncture points with regard to three commonly held tenets of acupuncture: (1) EDA at pathology-related acupuncture points is distinguishable from nonpathology-related acupuncture points; (2) EDA at acupuncture points can assist in diagnosing and monitoring therapeutic progress; and (3) EDA at acupuncture points is able to identify substances that are either therapeutically benefi cial or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…34 In a recent narrative review, the relation of acupuncture point electrodermal activity to pathology has been described. 35 In this review one blinded study found that electrodermal activity at auricular acupuncture points could be used to distinguish which patients had recent or prior cardiopathology and which were healthy control subjects. 36 The observation that traditional pathways of acupuncture meridians correspond to ultrasound images of connective tissue planes 30 has been followed by the insight that these meridian-oriented collagenous structures are associated with lower electrical impedance.…”
Section: Fundingmentioning
confidence: 99%
“…34 In a recent narrative review, the relation of acupuncture point electrodermal activity to pathology has been described. 35 In this review one blinded study found that electrodermal activity at auricular acupuncture points could be used to distinguish which patients had recent or prior cardiopathology and which were healthy control subjects. 36 The observation that traditional pathways of acupuncture meridians correspond to ultrasound images of connective tissue planes 30 has been followed by the insight that these meridian-oriented collagenous structures are associated with lower electrical impedance.…”
Section: Fundingmentioning
confidence: 99%
“…This review also highlighted the heterogeneity of approaches to EDA assessments and the discrepancies between common clinical practice and the scientific evidence to support that practice. 33 Therefore, although some types of instruments for acupoints' electrical conductance measurement are available on the market-and are used by some acupuncturists to help diagnose Qi imbalance, guide treatment strategies, and evaluate treatment outcomes-reliable and wide use of these instruments in patient care deserves further investigation. 33 About 5 years ago, a multichannel system for continuous measurement of skin resistance and capacitance at acupoints was developed in a research setting for obtaining accurate and reliable measurements.…”
Section: Reactions At the Acupoints When Needling Is Performedmentioning
confidence: 99%
“…While the physiological mechanisms underlying acupuncture have yet to be unambiguously identified, the balance of evidence favours quantitative differences in electrodermal properties between acupuncture points and surrounding skin [29,30]. There is also emerging evidence of correlations between connective tissue anatomy, microcirculatory blood flow, and acupuncture needling points [31].…”
Section: Introductionmentioning
confidence: 99%